The importance of digital transformation technology formulas in developing the performance of the hotel sector in Iraq - Dr. Ghania Diaa Mashfi (Peerian Journals Publishing, 2023)
This research seeks to study the impact of digital transformation technology in the development of the hotel sector in Iraq, and this impact appears clearly by changing , developing and developing ways of providing services to tourists, to increase the ability to improve productivity and competitiveness and reduce costs and quality of services in order to raise and support the performance of the tourism and hotel sector in Iraq by providing a high level of services provided to tourists, One of the most important conclusions reached by the researcher is that digital technology helps increase the ability to meet demand in the peak season, and the most important recommendations that tourist hotels should rely on all forms of digital technological transformation to increase competitiveness
Keywords: Digital transformation technology; development of the hotel sector